(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
ABSTRACT This study examines strategies for selecting instructional media based on an analysis of learning objectives and learner characteristics within the context of modern education, which demands more adaptive and effective instructional approaches. The research problem focuses on how media can be chosen appropriately by considering instructional goals, individual learner characteristics, and contextual conditions of learning. The research questions include: (1) how learner characteristics influence the selection of instructional media; (2) how learning objectives and materials determine the appropriate type of media; and (3) how contextual factors and resource availability affect media-selection decisions. This study employs a literature review method through an analysis of journal articles, academic books, and relevant research reports published within the last ten years. The findings indicate that effective media selection must consider the alignment between students’ learning styles, prior knowledge, and individual needs with the types of media used. Media aligned with instructional objectives are shown to enhance conceptual understanding, motivation, and learner engagement. Additionally, learning materials that are abstract, applicative, or contextual require different types of media to facilitate optimal comprehension. Contextual factors such as teacher competence, infrastructure, time allocation, and technological availability also influence the feasibility of media implementation. This study proposes a conceptual model that positions three key components learner characteristics, learning objectives and materials, and contextual resources as the basis for a cyclical decision-making process in instructional media selection. The model contributes to strengthening instructional design practices grounded in more systematic and context-responsive needs analysis. ABSTRAK Penelitian ini mengkaji strategi pemilihan media pembelajaran berdasarkan analisis tujuan pembelajaran dan karakteristik peserta didik dalam konteks pendidikan modern yang menuntut pendekatan instruksional lebih adaptif dan efektif. Rumusan masalah penelitian berfokus pada bagaimana media dapat dipilih secara tepat dengan mempertimbangkan tujuan instruksional, karakteristik individu peserta didik, dan kondisi kontekstual pembelajaran. Pertanyaan penelitiannya ialah: (1) bagaimana karakteristik peserta didik mempengaruhi pemilihan media pembelajaran; (2) bagaimana tujuan dan materi pembelajaran menentukan jenis media yang sesuai; dan (3) bagaimana konteks serta ketersediaan sumber daya memengaruhi keputusan pemilihan media. Penelitian ini menggunakan metode studi literatur melalui analisis terhadap artikel jurnal, buku akademik, dan laporan penelitian yang relevan dalam sepuluh tahun terakhir. Hasil kajian menunjukkan bahwa pemilihan media yang efektif harus memperhatikan kesesuaian antara gaya belajar, kemampuan awal, dan kebutuhan siswa dengan jenis media yang digunakan. Media yang selaras dengan tujuan pembelajaran terbukti lebih mampu meningkatkan pemahaman konseptual, motivasi, dan keterlibatan peserta didik. Selain itu, materi pembelajaran yang bersifat abstrak, aplikatif, atau kontekstual memerlukan jenis media yang berbeda agar dapat dipahami secara optimal. Faktor kontekstual seperti kompetensi guru, sarana prasarana, waktu, serta ketersediaan teknologi turut menentukan kelayakan implementasi media. Penelitian ini menghasilkan model konseptual yang menempatkan tiga komponen utama karakteristik peserta didik, tujuan serta materi pembelajaran, dan konteks sumber daya sebagai dasar siklus pengambilan keputusan media pembelajaran. Model ini berkontribusi pada penguatan praktik desain pembelajaran berbasis analisis kebutuhan yang lebih sistematis dan kontekstual.